1) –39
2) –9
3) –406
Пошаговое объяснение:
ну так вроде
1) Минус перед скобками меняет знаки:
-(59 - 69) - 29 = - 59 + 69 - 29 = - 19
2) Аналогично:
- (284 - 49 - 244) = -284 + 49 + 244 = 9
3) Плюс перед скобками занки не меняет:
(- 34 - 410 ) + 38 = - 34 - 410 + 38 = - 406
1) –39
2) –9
3) –406
Пошаговое объяснение:
ну так вроде
Пошаговое объяснение:
1) Минус перед скобками меняет знаки:
-(59 - 69) - 29 = - 59 + 69 - 29 = - 19
2) Аналогично:
- (284 - 49 - 244) = -284 + 49 + 244 = 9
3) Плюс перед скобками занки не меняет:
(- 34 - 410 ) + 38 = - 34 - 410 + 38 = - 406